Selection, Firm Turnover, and Productivity Growth : Do Emerging Cities Speed Up the Process? - Jones, Patricia; Mengistae, Taye; Zeufack, Albert (World Bank, Washington, DC, 2018)
This paper identifies and estimates the impact of firm entry and exit on plant-level productivity in Ethiopia as part of a selection mechanism that might be driving aggregate productivity growth in cities. Specifically, the paper investigates how firms’ entry and exit contribute to the pace of factor reallocation and total factor productivity growth within industries—and whether these processes occur in higher numbers and rates in larger cities. The analysis is carried out using establishment census data from Ethiopia that cover the period from year 2000 to 2010. Importantly, these data include information on plants’ physical outputs and their prices, which allows distinguishing between revenue-based measures of total factor productivity (TFPR) and those based on physical productivity (TFPQ). The analysis reveals that these two measures generate very different results under imperfect competition, suggesting that physical productivity measures (TFPQ) are better suited to examining firm dynamics when local producers have some degree of market power. In addition, the findings show that less productive (higher cost) firms are more likely to exit than their more productive (lower cost) rivals—but the analysis controls for producers’ transport costs. This is consistent with the probability of firm exit being higher when transport costs are lower.